IceTop: The surface component of IceCube - Abbasi, R.; Abdou, Y.; Ackermann, M.; Adams, J.; Aguilar, J.; Ahlers, M.; Altmann, D.; Andeen, K.; Auffenberg, J.; Bai, X.; Baker, M.; Barwick, S.; et al. (2013)
IceTop, the surface component of the IceCube Neutrino Observatory at the South Pole, is an air shower array with an area of 1 km2. The detector allows a detailed exploration of the mass composition of primary cosmic rays in the energy range from about 100 TeV to 1 EeV by exploiting the correlation between the shower energy measured in IceTop and the energy deposited by muons in the deep ice. In this paper we report on the technical design, construction and installation, the trigger and data acquisition systems as well as the software framework for calibration, reconstruction and simulation. Finally the first experience from commissioning and operating the detector and the performance as an air shower detector will be discussed.